2020
DOI: 10.2196/20283
|View full text |Cite
|
Sign up to set email alerts
|

Rates of Attrition and Dropout in App-Based Interventions for Chronic Disease: Systematic Review and Meta-Analysis

Abstract: Background Chronic disease represents a large and growing burden to the health care system worldwide. One method of managing this burden is the use of app-based interventions; however attrition, defined as lack of patient use of the intervention, is an issue for these interventions. While many apps have been developed, there is some evidence that they have significant issues with sustained use, with up to 98% of people only using the app for a short time before dropping out and/or dropping use down… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
171
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 294 publications
(220 citation statements)
references
References 31 publications
19
171
3
Order By: Relevance
“…Of the 1964 participants who enrolled in the program, 1070 (54.5%) did not meet our definition for active participation at 12 weeks. This is consistent with attrition rates for other digital diabetes interventions reflected in published observational studies [ 51 ]. Of those participants remaining in the sample, 668 (34.0%) failed to complete the surveys defined in the inclusion criteria for this study, which were optional for completing the program.…”
Section: Resultssupporting
confidence: 89%
“…Of the 1964 participants who enrolled in the program, 1070 (54.5%) did not meet our definition for active participation at 12 weeks. This is consistent with attrition rates for other digital diabetes interventions reflected in published observational studies [ 51 ]. Of those participants remaining in the sample, 668 (34.0%) failed to complete the surveys defined in the inclusion criteria for this study, which were optional for completing the program.…”
Section: Resultssupporting
confidence: 89%
“…However, this design is not possible in randomized studies comparing different types of treatment (eg, comparing the effectiveness of lobectomy and radiosurgery in early lung cancer). Limitations such as these necessitate the identification of clinical reasoning, complemented by meta-analyses involving observational studies [ 19 , 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…Acceptability of mobile phone apps has been shown to be high among users [53]. Participant engagement with the challenge was substantial; nevertheless, our challenge was short and prior literature suggests a decrease in adherence to these solutions over time [56][57][58]. Therefore, when using these strategies to help exercise engagement among breast cancer patients with fatigue, it will be important to include elements such as the usability of the technology, motivating factors, data monitoring, personal contact with the study personnel/support, and personalized feedback that has shown before to contribute to better adherence [59].…”
Section: Principal Findingsmentioning
confidence: 88%